Akuisisi bahan pustaka pada Perpustakaan Akademi Film Yogyakarta - Dedy Hermawan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
ABSTRACT The discussion of this article is about the acquisition of library materials with a study study at the Yogyakarta Film Academy Library. The purpose of this determination is to determine the acquisition of library materials in the library. The method used in this research is a qualitative method. Qualitative methods focus attention to a variety of methods, using triangulation methods that reflect efforts to gain a deep understanding of the phenomenon under study. The results of this study indicate that the acquisition or procurement of library materials carried out by the Yogyakarta Film Academy library carries out acquisition activities using the process of buying, giving or gifts, and cooperation. The three acquisition activities are considered effective to increase the collection in the library. It is suggested that the process of library material acquisition activities be further improved in terms of purchasing, gifts, and cooperation. Collaboration that is not limited to university libraries, public libraries or other related institutions. There is still a lot of work and library material acquisition activities that have not been carried out by the Yogyakarta Film Academy libraries, such as exchanges, deposits, and self-publishing. Keywords: Acquisition, Library material, Collection development, Library ABSTRAK Pembahasan artikel ini adalah mengenai akuisisi bahan pustaka dengan studi kajian pada Perpustakaan Akademi Film Yogyakarta. Tujuan dari penetian ini yakni guna mengetahui kegiatan akusisi bahan pustaka di perpustakaan. Metode yang digunakan pada penelitian ini merupakan metode kualitatif. Metode kualitatif berfokus perhatian kepada berbagai macam metode, penggunaan metode triangulasi yang mencerminkan upaya guna memperoleh pemahaman yang mendalam terhadap suatu fenomena yang diteliti. Hasil penelitian ini menunjukkan bahwa kegiatan akuisisi atau pengadaan bahan pustaka yang dilakukan oleh perpustakaan Akademi Film Yogyakarta melakukan kegiatan akuisisi dengan menggunakan proses pembelian, pemberian atau hadiah, serta kerjasama. Ketiga kegiatan akuisisi tersebut dinilai efektif untuk memperbanyak koleksi pada perpustakaan. Disarankan agar proses kegiatan akuisisi bahan pustaka lebih ditingkatkan dari sisi pembelian, hadiah, dan kerjasama. Kerjasama yang tidak terbatas kepada perpustakaan perguruan tinggi, perpustakaan umum ataupun lembaga-lembaga lain yang terkait. Masih banyak pekerjaan serta kegiatan akuisisi bahan pustaka yang belum dilakukan oleh perpustakaan Akademi Film Yogyakarta seperti tukar menukar, titipan, dan terbitan sendiri. Kata Kunci: Akuisisi, Bahan Pustaka, Pengembangan Koleksi, Perpustakaan